Severe acute cellular rejection after intestinal transplantation is associated with poor patient and graft survival. Issue 5 (31st March 2017) - Huard, Genevieve; Schiano, Thomas D.; Moon, Jang; Iyer, Kishore
Abstract: Background: Severe acute cellular rejection (ACR) occurs frequently after intestinal transplantation (ITx). Aim: To evaluate the outcomes and the risk factors for graft failure and mortality in patients with severe ACR after ITx. Methods: Retrospective study evaluating all ITx recipients who developed severe ACR between 01/2000 and 07/2014. Demographic and histologic data were reviewed. Results: 20/126 (15.9%) ITx recipients developed severe ACR. Of these 20 episodes, 13 were in adults (median age: 47.1). The median (IQR) time from ITx to severe ACR was 206.5 (849) days. All patients received intravenous methylprednisolone and increased doses of tacrolimus. Sixteen (80%) patients did not respond to initial treatment and required thymoglobulin administration. Moreover, 11 (55%) patients required additional immunosuppressive medications. Six (30%) patients required graft enterectomy. Complications related to ACR treatment were the following: 10 (50%) patients developed bacterial infections, four (20%) patients developed cytomegalovirus infection and four (20%) patients developed post‐transplant lymphoproliferative disease. At the end of follow‐up, only 3/20 (15%) were alive with a functional allograft. The median patient survival time after diagnosis of severe ACR was 400 days (95% CI: 234.0‐2613.0). Conclusions: Severe ACR episodes are associated with high rates of graft loss and complications related to treatment.